Impact of Single‐ vs. Split‐Dose Low‐Volume Bowel Preparations on Bowel Movement Kinetics, Patient Inconvenience, and Polyp Detection: A Prospective Trial. (September 2016) - Horton, Nicholas; Garber, Ari; Hasson, Henrietta; Lopez, Rocio; Burke, Carol A
Abstract : OBJECTIVES: There are little data on bowel movement (BM) kinetics induced by bowel preparation. Whether single‐dose (SID) or split‐dose (SPD) regimens differ in terms of patient convenience is unclear. We compared BM kinetics, sleep and travel disruptions, and polyp detection rates in patients undergoing colonoscopy assigned to SID vs. SPDs. METHODS: Patients were randomly assigned to 2‐L SID or SPD (SPD1 and SPD2) bowel preparations. Surveys were completed querying the onset, duration, cessation, and intensity of BMs, along with sleep and travel disruption en route to the endoscopy center. Colon cleansing quality and polyp histology were recorded. RESULTS: A total of 341 patients were enrolled, 51% in SPD and 49% in SID. Over half of patients had their first BM within 60 min of starting the preparation. After dosing, 92% of SID and 66% of SPD1 patients achieved clear effluent ( P <0.001), whereas it was reported in 97% of SPD2 patients ( P =0.028 vs. SID). Total duration ( P =0.041) and intensity ( P <0.001) of BMs were greater in SID. More patients in SID woke up for BMs (65.9 vs. 48.8%, P <0.003). No differences in the need to stop driving en route to colonoscopy were noted. Bowel prep quality was better in SPD ( P <0.001). Although no difference in the adenoma detection rate was noted, the sessile‐serrated polyp detection rate was greater in SPD than in SID (9.9 vs. 2.4%, P =0.004). CONCLUSIONS: Our data demonstrate that SPD bowel preparation results in decreased intensity and duration of BMs, less patient inconvenience, improved bowel preparation, and increased sessile‐serrated polyp detection rates.